Islam and Religious Moderation Analysis of Maudhu'i Tafsir - Fitria, Intan Yulia; Sutantio, Heri; Fauzi, Husni Taftazani (Jurnal Ilmiah Teunuleh, 2024)
Religious moderation in Islam is a middle attitude that is practiced in beliefs, attitudes, behavior and practices in religion. Religious moderation as mentioned in the Qur'an is the basis for the ummah to create peace, tolerance and justice in society. The research method used in this study is a literature review using the Tafsir Maudu'i approach. The meaning of religious moderation is explained in several languages with a focus on the meaning of words containing the concepts of moderation, balance and mediation in religious practice. Al-Qur'an verses that discuss religious moderation, such as QS. Al-Baqarah verse 143, QS. Al-Hujurat verse 13 and QS. Al-Baqarah verse 238, analyzed to understand the messages contained in it in order to understand the importance of maintaining balance in beliefs, attitudes and social interactions. The results of this research show that religious moderation is one of the important aspects in maintaining harmony and justice in society. By understanding and implementing the principle of moderation, religious communities can live side by side peacefully and respect differences.